The Relationship Between Cigarette Smoke Exposure, Nutritional Status, and Preschool Children's Development - Hasni, Hasni; Evie, Sova; Nurmiaty, Nurmiaty; Enggar, Enggar; Ra'bung, Alfrida Semuel; Saman, Saman; Suswinarto, Dwi Yogyo; Azwar, Azwar (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Pre-school age children are an important period, because this period is the basis that determines a child's future development. Therefore, it is important to pay attention to the nutritional status of pre-school children. Proper and balanced nutritional intake will affect children's development, growth and intelligence. Likewise, exposure to cigarette smoke can result in loss of appetite in children, which has a negative impact on child development, including increasing the risk of stunting. The aim of this study was to determine the relationship between exposure to cigarette smoke, nutritional status and development of preschool children. The aim of this study was to determine the relationship between exposure to cigarette smoke and nutritional status on the development of preschool children. This research uses a correlational analytical design with a cross sectional approach, to see the relationship between the independent variables, namely exposure to cigarette smoke and nutritional status, to the dependent variable, namely the development of preschool children, using the chi-square test. In 76 samples, the period from February to March 2024. The results of the correlation test show that there is a significant relationship between the independent variable, namely exposure to cigarette smoke and nutritional status, to the dependent variable, namely the development of preschool children. This is indicated by a smaller significant value (p-value). from a significance level of 5%. Conclusion: There is a significant relationship between cigarette smoke exposure and the nutritional status and development of preschool children. It is important for parents to pay attention to their children's nutritional intake and for the Regional Government to consider establishing a Smoke-Free Area.